Exploring Figurative Language in a “How Make Millions Before Grandma Dies” Film - Sinaga, Eunike Angita; Manik, Sondang; Pasaribu, Arsen Nahum (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
The purpose of this study is to analyze the figurative language used in the film entitled "How to Make Millions Before Grandma Dies". Data were taken from the video conversation of the film "How to Make Millions Before Grandma Dies". Using a qualitative descriptive research method, the researcher analyzed the interpretation of six types of figurative language, namely metaphor, simile, personification, irony, hyperbole, and euphemism. The results of the study through the analysis of figurative language in the film showed that there were 138 data grouped based on the type of figurative language analysis consisting of 69 metaphors, 7 similes, 23 personifications, 14 ironies, 19 hyperbole and 6 euphemism. It can be concluded that in the film metaphor is the dominant type of figurative language in the film's dialogue. Therefore, this study can help readers, especially teachers and students, in understanding the analysis of figurative language theory in films.